2020
DOI: 10.1097/md.0000000000019930
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus associated hepatic smooth muscle tumor in a patient with acquired immunodeficiency syndrome

Abstract: Introduction: Epstein-Barr virus (EBV) associated smooth muscle tumors (SMTs) usually present under the condition of immunosuppression, including congenital immunodeficiency syndrome-SMT, post-transplantation-SMT and HIV-SMT. HIV-SMTs are most likely to invade the central nervous system, followed by the liver, lungs, and other locations. [ 1 ] Many laboratory techniques, including serological techniques, polymerase chain reaction and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In as many as 90% of patients with EBV-SMT, death is secondary to opportunistic infections rather than tumor burden [4,6] . There are few reports of disseminated cryptococcal infection or cryptococcal meningitis occurring concomitantly in a patient with EBV-SMT(s) of the CNS [7–9] . To our knowledge, there has not been any previously described cases of EBV-SMT with infectious organisms present within the tumor matrix, such as seen in this case.…”
Section: Discussionmentioning
confidence: 69%
“…In as many as 90% of patients with EBV-SMT, death is secondary to opportunistic infections rather than tumor burden [4,6] . There are few reports of disseminated cryptococcal infection or cryptococcal meningitis occurring concomitantly in a patient with EBV-SMT(s) of the CNS [7–9] . To our knowledge, there has not been any previously described cases of EBV-SMT with infectious organisms present within the tumor matrix, such as seen in this case.…”
Section: Discussionmentioning
confidence: 69%
“…The gold standard for diagnosing EBV-SMT is EBV-encoded small RNA in situ hybridization because immunohistochemistry alone has a rather low sensitivity ( Magg et al., 2018 ). It is particularly important to establish an algorithm for the pathological diagnosis of spindle cell tumors in HIV patients, as other differential diagnoses include Kaposi sarcoma, myopericytoma, gastrointestinal stromal tumor, and mycobacterial spindle cell pseudotumor ( Zhou et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…While some cases reported that combination with surgical resection and ART achieved complete remission in AIDS related EBV-SMTs [4,5], case reports of ART alone were extremely rare. Previous case reports of ART alone for AIDS related EBV-SMTs are summarized in Table 1 [12][13][14]. Unfortunately, it is difficult to evaluate the effectiveness of ART alone for AIDS related EBV-SMTs from these cases.…”
Section: Discussionmentioning
confidence: 99%